Pengembangan “Pasiraman Pura Dalem Pingit Dan Pura Kusti” Sebagai Daya Tarik Wisata Spiritual Di Desa Batuan Gianyar - I Made Darma Oka; Made Sudiarta; I Gede Astawa; I Wayan Sukita (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2021)
The aims of this paper to analyze the feasibility of “Pasiraman Pura Dalem Pingit and Pura Kusti” to develop into tourist attractions-based tourism destination components aspect, such as attractions, accessibility, amenities, and ancillary service. Observation data, interviews, and literature study method with qualitative descriptive analysis used in this paper. It is shown that “Pasiraman Pura Dalem Pingit and Pura Kusti” feasible to develop into tourist attraction to be an alternatives when choose the tourist attraction. This feasibility is seen by the tourism facilities component are owned, such as: Temples as place of worship, places to do “melukat”, parking lots, restaurants, fitting rooms, toilets, shelters, and “puskesmas” in village area. Tourists that visiting tourist attraction not only see the beauty of the natural panorama or the uniqueness of the local culture but directly involved spiritual tourism activities. For this reason, this tourist attraction suggested to manage professionally and sustainable so it can compete with the others.